Welnu dan Eet Ik Jou op: Bergelut dengan Serangan Belalang Kayu di Jawa (1878-1937) - Ardhiatama Purnama Aji (Lembaran Sejarah, 2023)
This article describes a number of series of wood locust attacks in Java from 1878 until 1937. With the application of the historical method, this research resulted in findings that wood locusts attacked several areas, such as Boyolali (1898), Banyumas (1898), Grobogan (1915), Semarang (1915), Salatiga (1915), Gunung Kidul (1915), Ngawi (1937), and Nganjuk (1937). Wood locust attacks damaged crops such as corn, coconut, tobacco, opium, and teak. The colonial government then took serious steps by appointing experts, publishing research results, providing information services, issuing instructions for eradicating locust eggs, and deploying natural enemies of wood locusts such as mushrooms, wasps and beetles. Even though it had subsided after 1917, thousands of locusts attacked again in 1937 in Ngawi and Nganjuk. However, because the government’s role was considered to be less significant, the people who were suffering then took other means. By lighting torches, they hunted wood locusts at night and made their wood locusts as a side dish to complement rice.